2000
DOI: 10.1007/s11746-000-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

Demulsification of oil‐in‐water emulsion under freezing conditions: Effect of crystal structure modifier

Abstract: The demulsification of oil-in-water (O/W) emulsions under freezing conditions is connected to fat crystallization in the oil droplet. Therefore, demulsification can be prevented by the use of oil with a low melting point, and also by lowering the O/W ratio. However, an oil with a low melting point, such as sunflower, is rather expensive, and the O/W ratio has a significant effect on the texture of emulsions. We searched for an oil that is suitable for the production of a freeze-stable emulsion and found that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…In addition, several small-molecule surfactants can partly dissolve in the oil and may then affect the crystallisation behaviour in the globules [84,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Small-molecules surfactants can affect nucleation, crystal growth and/or the polymorphic transitions, dependent on their miscibility in the oil [23].…”
Section: Small-molecule Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several small-molecule surfactants can partly dissolve in the oil and may then affect the crystallisation behaviour in the globules [84,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Small-molecules surfactants can affect nucleation, crystal growth and/or the polymorphic transitions, dependent on their miscibility in the oil [23].…”
Section: Small-molecule Surfactantsmentioning
confidence: 99%
“…Small-molecules surfactants can affect nucleation, crystal growth and/or the polymorphic transitions, dependent on their miscibility in the oil [23]. As a consequence the amount, the size, the morphology and the sintering of the crystals, the arrangement of the crystals in the globule, the fat crystal network and the SFC can depend on the type and the concentration of the surfactants and can, thereby, affect the partial coalescence stability of the emulsions [39,84,89,102,103].…”
Section: Small-molecule Surfactantsmentioning
confidence: 99%
“…There are a number of reports on the effects of emulsifiers on crystal morphology (28)(29)(30)(31), and the size of the crystal is associated with the crystal form; b-form tends to produce granular crystals and b is recommended for producing small crystals. In the present study, we observed that palm oil with polyglycerol behenic acid esters added, the b -form is preferentially crystallized, and the crystal does not grow to a granular crystal.…”
Section: Effects Of Adding Polyglycerol Behenic Acid Estersmentioning
confidence: 99%
“…As for EAEP, water is as solvent which could mitigate the environmental impact comparing to solvent extraction. However, the demulsification has been seen as a critical step for oil recovery in aqueous extraction due to its high energy requirement especially on physical (Hagenmaier et al, 1972, Harada & Yokomizi, 2000, McClements, 2005 and chemical methods (Menon & Wasan, 1985).…”
Section: Fig 1 Expelling Solvent and Aqueous Processes Of Soybean Ementioning
confidence: 99%